Analysis of Traders' Welfare After the New Market Relocation in Tanjungpinang City - Iqlal Alfarez Sanjaya; Syahrul Ramadhan; Muhammad Zulfikri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Market relocation efforts are being made by the city government to renew the market so that it can provide safe, conducive and representative procedures. There are 800 traders to occupy the stalls which is done by lottery to minimize the emergence of social jealousy. This research uses a descriptive qualitative approach. This research uses snowball sampling to obtain data from traders to other traders. This research is located at the Puan Ramah Kijang Lama market. The problem found is the lack of special attention from the government in re-marketing the Puan Ramah market area. This lack of attention from the government has resulted in the traders' income being considered to be below their target or goal, so that the traders feel disappointed with the policies issued by the government and the traders hope that the government will focus on speeding up the process of renovating the new market.